Blurring Boundaries: Comparing Professional Journalism and Citizen Journalism in the Age of Social Media - Musa Adamu Labaran (Budapest International Research and Critics University, 2023)
The advent of the new media facilitated the creation, modifying and sharing of information among citizens. It is as a result of these that a participatory brand of journalism called citizen journalism came into existence. This paper interrogates the question of what is new about the new media, the influence of new media on conventional media, the internet as a global new media, new media, social media and online journalism, the concept of citizen journalism, perspectives on the practice of citizen journalism, and criticisms of citizen journalism. Based on the secondary data that was generated from the existing literature, the paper argues that the rise of social media has significantly transformed the landscape of journalism, leading to a growing convergence between professional journalism and citizen journalism. This paper explores how the boundaries between these two forms of journalism have become increasingly porous in the digital age. The paper points that the age of social media necessitates a redefinition of journalistic authority, suggesting a more hybrid model where collaboration and coexistence between professional and citizen journalists may shape the future of news production. The paper concludes that the rise of social media has significantly reshaped the landscape of journalism, eroding the once-clear distinctions between professional and citizen journalism. As citizens gain access to tools and platforms for immediate content creation and distribution, they increasingly participate in news production, especially during breaking events or crises. This shift challenges the monopoly of traditional media institutions on information dissemination and redefines the role of journalists in society.